Skyrme random-phase-approximation description of lowest Kπ= 2γ+ states in axially deformed nuclei - Nesterenko, V. O.; Kartavenko, V. G.; Kleinig, W.; Kvasil, J.; Repko, A.; Jolos, R. V.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2016)
The lowest quadrupole γ-vibrational Kπ=2+ states in axially deformed rare-earth (Nd, Sm, Gd, Dy, Er, Yb, Hf, W) and actinide (U) nuclei are systematically investigated within the separable random-phase-approximation (SRPA) based on the Skyrme functional. The energies Eγ and reduced transition probabilities B(E2) of 2γ+ states are calculated with the Skyrme forces SV-bas and SkM∗. The energies of two-quasiparticle configurations forming the SRPA basis are corrected by using the pairing blocking effect. This results in a systematic downshift of Eγ by 0.3-0.5 MeV and thus in a better agreement with the experiment, especially in Sm, Gd, Dy, Hf, and W regions. For other isotopic chains, a noticeable overestimation of Eγ and too weak collectivity of 2γ+ states still persist. It is shown that domains of nuclei with low and high 2γ+ collectivity are related to the structure of the lowest two-quasiparticle states and conservation of the Nilsson selection rules. The description of 2γ+ states with SV-bas and SkM∗ is similar in light rare-earth nuclei but deviates in heavier nuclei. However SV-bas much better reproduces the quadrupole deformation and energy of the isoscalar giant quadrupole resonance. The accuracy of SRPA is justified by comparison with exact RPA. The calculations suggest that a further development of the self-consistent calculation schemes is needed for a systematic satisfactory description of the 2γ+ states.
CRIS-Team Scopus Importer:2023-07-24